Notes to Philosophy 167: Class 3 -- Kepler's Astronomia Nova: The Orbit of Mars -- Part 1. - Smith, George E. (George Edwin), 1938- (Tufts Archival Research Center, 2015)
Synopsis: Overview of the Class: Planetary Astronomy -- Turning Data into Evidence: Evidential Arguments -- The Kepler of Legend: A Contemporary Version.; Generally corresponds to the video segment: Class 3, Part 1.